Magical Realistic Characteristics in the Novel the Miracle of Namiya Grocery Store by Keigo Higashino. - Risky Arbangi Nopi; Mukh Doyin; Bernardus Wahyudi Joko Santoso (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Novel The Miracle of Namiya Grocery Store is a literary work that depicts magical realism through its characters and narrative events. The story presents unique characters and magical phenomena that involve the disruption of time, space, and identity, creating a blend of reality and fantasy. This research focuses on the interactions between the characters and the magical events they experience in the grocery store, which serves as a medium for communication across time. This study applies to a sociological approach to literature, using the theory of magical realism. Data were collected through heuristic semiotic reading and analyzed using hermeneutic semiotic reading. The results reveal six main characteristics of magical realism: irreducible elements, a phenomenal world, disturbing doubts, the fusion of realism and magic, the disruption of time and space, and a moral message conveyed through magical events. Magical elements—such as the letter from the past—serve as a subtle yet powerful way to convey moral values such as empathy, hope, forgiveness, and solidarity. This research concludes that magical realism not only enriches the story aesthetically but also deepens its moral impact. This study is expected to support literary learning, inspire further research on local magical traditions, and assist educators in developing materials that enhance students' critical thinking skills.